Full dynamic transformation model for spatial data from relational database to object-oriented database - Siew, Teck Kiong (Faculty of Computer Science and Information Technology, 2005)
In the present database technology, classical data models have proven to have limitations in modeling spatial data in many aspects while the up surging of the object-oriented database technology in the latest computer technology seems to be the most promising approach to deal with today's complex application.